High mid-treatment tumour RNA disruption in patients with HER2-negative breast cancer is associated with improved disease-free survival after neoadjuvant chemotherapy - Amadeo M. Parissenti; Laura B. Pritzker; Maria Aanesland Dahle; Hedda von der Lippe Gythfeldt; Twinkle Masilamani; Gabriel Theriault; Renée St-Onge; Lavina D’costa; Ole Christian Lingjaerde; Mads Haugland Haugen; Olav Engebraaten (Breast Cancer Research)
Abstract Background High tumour ribosomal RNA degradation (RNA disruption) during neoadjuvant chemotherapy has been associated with a post-treatment pathologic complete response (pCR) and improved disease-free survival (DFS) in breast cancer patients. We further assessed the relationship between tumour RNA disruption or other metrics and neoadjuvant chemotherapy outcome using data from the NeoAva clinical trial (NCT00773695). Methods Patients with early HER2-negative breast cancer received FEC-T chemotherapy ± bevacizumab in a randomized fashion. Biopsies were taken pre-treatment and after 12 and 25 weeks of chemotherapy. RNA and proteins extracted from the biopsies were used to compute the RNA disruption index (RDI) and to quantify levels of 210 proteins using protein array analysis at 12 weeks. Results Tumour RDI values were higher mid- and post-treatment than pre-treatment (p < 0.0001). Patients with tumour RDI values > 1.1 exhibited higher disease-free and breast cancer-specific survival than patients with RDI values ≤ 1.1 (p = 0.049 and 0.031, respectively). While RDI values were higher for patients on the bevacizumab-containing regimen (p = 0.003), this was not associated with improved survival. Survival on either regimen was not significantly associated with a post-treatment pCR or an improved residual cancer burden (RCB) score. Significant differences in apoptotic, EMT, Notch, G1-S checkpoint, and DNA damage response pathways were seen between high- and low-RDI tumours. Conclusions High tumour RNA disruption during neoadjuvant chemotherapy was associated with improved DFS and may better predict outcome than the post-treatment pCR rate or RCB. If validated as an independent predictor of chemotherapy outcome, RNA disruption assessments during treatment may prove informative in making treatment escalation or de-escalation decisions.